Falcão Junior, M.J.A., Pinto, R.B. & Mansano, V.F. (2016) A Taxonomic Revision of the genus Dialium (Leguminosae: Dialiinae) in the Neotropics. Phytotaxa 283 (2): 123–142. - Junior, Marcus José De Azevedo Falcão; Pinto, Rafael Barbosa; Mansano, Vidal De Freitas (Phytotaxa, 2016)
N/A